Acquired parvalbumin‐selective interneuronopathy in the multiple‐hit model of infantile spasms: A putative basis for the partial responsiveness to vigabatrin analogs?. (20th November 2018) - Katsarou, Anna‐Maria; Li, Qianyun; Liu, Wei; Moshé, Solomon L.; Galanopoulou, Aristea S.
Summary: West syndrome, an age‐specific epileptic encephalopathy, manifests with infantile spasms (IS) and impaired neurodevelopmental outcomes and epilepsy. The multiple‐hit rat model of IS is a chronic model of IS due to structural etiology, in which spasms respond partially to vigabatrin analogs. Using this model, we investigated whether IS due to structural etiology may have deficits in parvalbumin (PRV) and somatostatin (SST) immunoreactive (‐ir) interneurons, and calretinin‐ir (CR‐ir) neurons of the primary somatosensory cortex of postnatal day (PN) 20–24 rats, using specific immunohistochemical assays. PN3 Sprague‐Dawley male rats underwent the multiple‐hit induction protocol, were monitored until PN20–24, and were transcardially perfused to collect brains for histology. Age‐matched sham and naive control male rats were also used. Coronal brain cryosections were stained with anti‐PRV, anti‐CR, and anti‐SST antibodies, and regions of interest (ROIs) from the primary somatosensory cortices were selected to determine PRV‐, CR‐, and SST‐ir cell counts and cortical ROI volumes, with blinding to experimental group. Statistical analyses were done using a linear mixed model accounting for repeated measures. We found PRV‐ir interneuronal selective reduction, sparing of the CR‐ir and SST‐ir neurons, and bilateral cortical atrophy. Our findings provide evidence for acquired PRV‐selective interneuronopathy, possibly underlying the pathogenesis of IS, neurodevelopmental deficits, and epilepsy, and potentially contributing to the partial response to vigabatrin analogs in this model.